Un nouveau départ pour les dommages-intérêts punitifs - Grammond, Sébastien (Revue générale de droit, 2012)
Punitive damages have always attracted a lukewarm reception in Quebec law. This article analyses the recent de Montigny and Ward judgments of the Supreme Court, which resolve some important issues about which Quebec doctrine and case law were divided. First, the Supreme Court stated that punitive damages constitute an autonomous remedy that may be sought independently of a condemnation in compensatory damages. It also held that punitive damages may pursue the goals of punishment, deterrence and denunciation. Lastly, the Court sends a message of moderation as regards the quantum of punitive damages.